Variable viscosity effects on third-grade liquid flow in post-treatment analysis of wire coating in the presence of nanoparticles. Issue 10 (1st October 2018) - Mahanthesh, B.; Gireesha, B.J.; Archana, M.; Hayat, Tasawar; Alsaedi, Ahmed
Abstract : Purpose: The features of coated wire product are measured by the flow and heat transport occurring in the interior of dies. Therefore, an understanding of characteristics of polymers momentum, heat mass transfer and wall shear stress is of great interest. Enhancement of heat transfer rate is fundamental need of wire coating process. Therefore, this study aims to investigate the effect of suspended nanoparticles in heat and mass transport phenomena of third-grade liquid in post-treatment of wire coating process. Buongiorno model for nanofluid is adopted. Two cases of temperature dependent viscosity are considered. Design/methodology/approach: The governing equations are modelled with the help of steady-state conservation equations of mass, momentum, energy and nanoparticle concentration. Some appropriate dimensionless variables are introduced. Numerical solutions for the nonlinear problem are developed through Runge–Kutta–Fehlberg technique. The outcome of sundry variables for dimensionless flow, thermal and nanoparticle volume fraction fields are scrutinised through graphical illustrations. Findings: The study's numerical results disclose that the force on the total wire surface and shear stress at the surface in case of Reynolds Model dominate Vogel's Model case. Impact of nanoparticles is constructive for force on the total wire surface and shear stress at the surface. The velocity of the coating material can be enhanced by the non-Newtonian property. Practical implications: This study may provide useful information to improve the wire coating technology. Originality/value: Effect of nanoparticles in wire coating analysis by using Brownian motion and thermophoresis slip mechanisms is investigated for the first time. Two different models for variable viscosity are used.